Design Of A Hybrid Diesel/PV/Wind/Battery System In Remote Areas - Gan, Chin Kim; Wirun, Prayun; Tan, Chee Wei; Meysam, Shamshiri (Praise Worthy Prize, 2014)
There are large number of the remote areas worldwide that are far and not connected to the utility grid. Eluvaitivu Island is an example in the remote area that is not connected to the mainland. Thus, there is a need for the independent power generation system to supply the load demand in the island. This paper assesses the potential of implementing the Hybrid Diesel/PV/Wind/Battery in Eluvaitivu Island using HOMER simulation software. In this regard, five different system configurations of Hybrid Diesel/PV/Wind with and without energy storage devices have been tested. HOMER simulation software is used to perform the feasibility study and to determine the optimized configuration of the Hybrid system. This leads to optimal configuration which has the lowest Cost of Energy (COE), producing the lowest excess of electricity and releases the smallest amount of carbon dioxides (CO2). The criteria of analysis include the total Net Present Cost (NPC), the COE, the excess of electricity and the CO2 emissions. The sensitivity analyses for the change of PV and diesel prices were also included in this paper. In the presence of global energy scenario, the price of the diesel fuels is expected to increase every year while the cost of the Solar PV is expected to decrease driven by the incentives provided by the government.